2020
DOI: 10.3389/fpsyt.2020.577871
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of Home-Setting Psychoeducation Interventions for Behavioral Changes in Dementia: Some Lessons for the COVID-19 Pandemic and Post-Pandemic Assistance

Abstract: Background Impacts of social isolation measures imposed by COVID-19 Pandemic on mental health and quality of life of older adults living with dementia and their caregivers remain unexplored. Studies have shown that psychoeducational and psychosocial interventions can manage behavioral and psychological symptoms in dementia (BPSD) and reduce the emotional burden on family members when applied in home-setting scenarios. Method a comprehensive systematic review of useful i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 80 publications
2
29
0
3
Order By: Relevance
“…Some of the important factors leading to abuse according to our study could be poor knowledge about managing BPSD among the caregivers, caregiver burden, restriction of autonomy, and limitations of virtual consultations. Various studies have reported the successful use of patient-tailored, home-based psycho-educational interventions delivered via user-friendly online platforms to handle behavioral disturbances in PwD and reduce mood as well as anxiety symptoms among their caregivers which have resulted in an improved quality of life of the dyad ( 41 ).…”
Section: Discussionmentioning
confidence: 99%
“…Some of the important factors leading to abuse according to our study could be poor knowledge about managing BPSD among the caregivers, caregiver burden, restriction of autonomy, and limitations of virtual consultations. Various studies have reported the successful use of patient-tailored, home-based psycho-educational interventions delivered via user-friendly online platforms to handle behavioral disturbances in PwD and reduce mood as well as anxiety symptoms among their caregivers which have resulted in an improved quality of life of the dyad ( 41 ).…”
Section: Discussionmentioning
confidence: 99%
“…This challenge to the psychological well-being in society will certainly be launched in increasing proportion to the ability to intervene and handle the symptoms of anxiety among the general public (Gurvich et al , 2020 ). It is therefore necessary to prepare suitable interventions to tackle the presumed growing psychological malaise and to carry out research that may provide important information for the mental health services (Alves et al , 2020 ). Interventions regarding the consequences of the COVID-19 outbreak can be interpreted as interventions to tackle the crisis (Dong & Bouey, 2020 ; Zgueb et al , 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…The result reveals that both children and their parents are satisfied with the robot-based contents. The home-based psychoeducation studies during the pandemic and post-pandemic period were also investigated [ 134 ]. Friendly-technological equipment is adopted, e.g.…”
Section: Robots In Covid-19mentioning
confidence: 99%